NILAI-NILAI KEARIFAN LOKAL SEBAGAI PEMBENTUK KARAKTER DALAM KUMPULAN CERITA RAKYAT DAERAH JAMBI KARYA THABRAN KAHAR DAN KAWAN-KAWAN (ANALISIS STRUKTURAL) - Ade Rahima; Lastiar Mulia Agustinus (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this research is to describe the values of local wisdom as a character formation found in the collection of Cerita Rakyat Daerah Jambi by Thabran Kahar. The author took two stories of Cerita Rakyat Daerah Jambi: (1) Pulau Jur, (2) Perpatih Nan Sebatang. These two stories represent 4 aspects as a character-shaped, (1) aspect of honesty, (2) aspects of positive thinking, (3) aspects of religion, (4) aspects of interacting politely. As a result, the values of local wisdom as a character shape found in the Cerita Rakyat Daerah Jambi by Thabran Kahar is very wide. Of the two chosen Jambi folklore people have four aspects as characters, (1) aspects of honest attitude, (2) aspects of positive thinking, (3) religious aspects, (4) aspects of interacting politely. These aspects found in quotes contained in the Cerita Rakyat Daerah Jambi by Thabran Kahar and friends. The results of research have 33 quotes related to aspects of local wisdom values as characters. Of these 33 aspects there are 11 aspects of honest attitude, 8 aspects of positive ways of thinking, 7 aspects of religious, and 7 aspects of interacting politely. Descriptive qualitative research are used as a technique to describe the values of local wisdom as a character forming in the Cerita Rakyat Daerah Jambi by Thabran Kahar (structural analysis)